School Kitchen Gardens as Examples of Participatory Environmental Education: Theoretical Presentation &Swot Analysis in 6 Schools in Cyprus - Πέτρου Στέλλα; Κορφιάτης Κωνσταντίνος (Education Sciences, 2020)
We explore the potential of SWOT analysis as a methodological tool for the recording of the strengths, the threats and the prospects of school kitchen-gardens projects. We approach school gardens as spaces suitable for collaboration, solidarity, trust and democratic decision-making. We collected data from six elementary school kitchen-garden projectsin Cyprus, which involved 95 students. It turned out that a school kitchen-garden could be just a decorative act, but it also could be a real life participatory project which can transform school relationships with the community, people’s relationships with the production and consumption of their food, as well as the social relationships between the members of a community.